KOMPETENSI GURU DALAM PENGEMBANGAN KETERAMPILAN MOTORIK KASAR ANAK USIA DINI BERDASARKAN KUALIFIKASI AKADEMIK - Widodo, Widodo (JIV-Jurnal Ilmiah Visi, 2017)
This article aims to discover the competence of early childhood teachers in developing early gross motor skills based on academic qualifications and find out the improvement efforts. This library research with qualitative descriptive approach, was conducted as from September 2016 through January 2017. The data obtained from internet and other resources were processed and analyzed qualitatively. The results indicate that the competence of early childhood teachers whose academic qualification of early childhood education is adequate, although there are differences in quality based on the study program. The competence of teachers whose academic qualification of other relevant educational and psychological degrees is not sufficient because their provision of knowledge is also lacking. This research recommends to revise the existing regulations stated in the Government Regulations and Ministry Regulations related to the provision of the early childhood teachers.